Staying Close to Home: The Effects of COVID-19 on the Plastic Surgery Residency Match. Issue 9 (September 2021) - Hollins, Andrew W.; Zhang, Gloria X.; Stoehr, Jenna R.; Atia, Andrew; Sergesketter, Amanda R.; Wickenheisser, Victoria A.; Ko, Jason H.; Phillips, Brett T.
Abstract : Background: The 2019 novel coronavirus created unique challenges for the integrated plastic surgery match. The goal of this study was to evaluate the trends of the 2020 and 2021 integrated plastic surgery match specifically related to the 2019 novel coronavirus. Methods: Three separate individual surveys were designed for integrated plastic surgery program directors and applicants from the 2021 to 2020 match. The surveys were distributed to the email addresses of applicants that applied to our institution's integrated residency program. Information of current interns and newly matched applicants from program websites and certified social media accounts were recorded. Results: We received completed surveys from 19 of the 69 program directors for a response rate of 27.5%. The survey for the 2020 and 2021 match applicants was completed by 25 and 68 applicants, respectively, for a response rate of 6.1% and 21.9%. There was a significant difference in the average number of completed virtual subinternships between applicants that did and did not successfully match into plastic surgery (1.48 versus 0.36, P = 0.01). The rate of students matching at their home institution was the highest in 2021 at 26% compared to 2020 (18%) and 2019 (15%). Conclusions: The results of this study demonstrate that applicants were more likely to match at programs with which they had established previous connections, including home institutions. Applicants also had a higher likelihood to match if they completed a virtual subinternship during the 2021 match. Learning points can be applied to the upcoming application cycle to improve the overall experience.